Molecular characterization of Pasteurella multocida pfhaB1 gene fragment from buffalo and cattle isolates from Nusa Tenggara Timur Indonesia - Ine Karni; Didik Handijatno; Lucia Tri Suwanti; Kusnoto Kusnoto; Jola Rahmahani; Wiwiek Tyasningsih (Aceh Journal of Animal Science, 2019)
Almost all regions in Nusa Tenggara Timur East Nusa Tenggara (NTT) Province Indonesia are endemic areas of Haemorragic Septicaemia (HS), which is caused by Pasteurella multocida  (P. multocida ) Serotypes B: 2. The fragment  pfhaB1gene is one of the virulence factors of P. multocida.The objective of this study was to determaine the phylogenetic, homology of P. multocidapfhaB1gene fragment of isolatedfrom Buffalo and Cattle in NTT. The P. multocida isolateswere re-cultured and further microscopic examined the biochemical tests, PCR, sequencing, homology, and phylogenetic relatedness test. P. multocida was observed as gram negative, coccobacilus, no growth on MacConkey Agar, does not produce H2S and gas, nonmotile and indole positive, does not produce urease enzymes, does not use citrate as a carbon source, does not ferment maltose and lactose but it does ferment glucose, sucrose and mannitol. ThepfhaB1gene fragmentfrom buffalo and cattle NTT isolates and also Katha strain vaccine showed DNA band 506 bp. P.multocida isolates from buffalo and cattle in NTT have 91% - 99% score homology with the comparative isolate. The isolate P. multocida from buffalo and cattle in NTT are in one cluster and their phylogenetic relatedness is close to isolates from Iran and India. It is concluded that the  pfhaB1gene fragmentof P. multocida from buffalo and cattle isolates have phylogenetic relatedness close and homolog with the other comparative isolates.    Keywords: Haemorrhagic Septicaemia; Nusa Tenggara Timur; Pasteurella multocida;  pfhaB1gene